2019
DOI: 10.21203/rs.2.12552/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Female clients’ gender preferences for frontline health workers who provide maternal, newborn and child health (MNCH) services at primary health care level in Nigeria

Abstract: Background In Nigeria, anecdotes abound that female clients, particularly within northern Nigeria, have gender-based preferences for frontline health workers (FLHWs) who provide healthcare services. This may adversely affect uptake of maternal newborn and child health services, especially at primary healthcare level in Nigeria, where a huge proportion of the Nigerian population and rural community members in particular, access healthcare services. This study explored female clients’ gender preferences for fro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Our study shows that caregivers visited the health facilities to seek health services for their children more than for themselves and one of the reasons mentioned during the focus group discussions was because of fear of being attended to by male health extension workers when they go to the health facilities which is regarded as a social taboo which makes the use of traditional birth attendants preferred option for care and delivery when pregnant This corroborates findings reported in other studies that female clients tend to prefer accessing maternal, newborn and child health services from female health workers, especially in primary healthcare settings [30][31][32]. A study in India reported that health facilities with higher availability of female health workers were found to be associated with higher maternal health care utilization than child health care utilization and suggested that improving gender parity in the health workforce especially in rural areas may improve maternal health care use [33].…”
Section: Discussionsupporting
confidence: 87%
“…Our study shows that caregivers visited the health facilities to seek health services for their children more than for themselves and one of the reasons mentioned during the focus group discussions was because of fear of being attended to by male health extension workers when they go to the health facilities which is regarded as a social taboo which makes the use of traditional birth attendants preferred option for care and delivery when pregnant This corroborates findings reported in other studies that female clients tend to prefer accessing maternal, newborn and child health services from female health workers, especially in primary healthcare settings [30][31][32]. A study in India reported that health facilities with higher availability of female health workers were found to be associated with higher maternal health care utilization than child health care utilization and suggested that improving gender parity in the health workforce especially in rural areas may improve maternal health care use [33].…”
Section: Discussionsupporting
confidence: 87%
“…The predilection of mothers towards consulting female health workers could also challenge them to seek knowledge about HIV-exposed infant immunization. 35 The predictive role of age and work experience could be attributed to the impact of cumulative experience and in-service training opportunities. Further, the finding of knowledge disparity between the professions, though this conflicts with reports from Ghana, 26 could reflect differences in pre-service curricula, roles, and responsibilities as well as access to continuing education opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the study setting, immunization services tend to be dominated by nurse/midwives, who are predominantly female. 34 , 35 Similarly, respondents who received prior training in infant immunization are more likely to counsel mothers living with HIV. In contrast, those without such training may avoid such encounters or refer mothers to their experienced colleagues.…”
Section: Discussionmentioning
confidence: 99%